Reinforced concrete building design project and project based learning: case study / Ahmad Iqbal Mazhafizi - Mazhafizi, Ahmad Iqbal (2021)
In a nutshell, the objective of the project which is to design main structural component of a building and also failure check are achieved. The design and calculation are done based on requirement of Uniform Building By-Law (UBBL). The design calculations of all the structural components are pass without any failure. This is achieved by considering the suitability of the diameter bar size used to ensure the strength of structural components. Besides, the bar size used are economical as they are not too big based on the as required from the structural components. Moreover, the size for each structural component is determined. It is determined by using assumptions formula for example the slab thickness is assumed using the formula of lx/d=30 + 30. However, the beam size estimated earlier needed to be change because of the failure occurred on the crack check. Changing the size of diameter bar could not help the beam to pass the cracking check thus, the beam size is changed to a bigger size compared to the size used by assumptions formula. The size of column used for design is based on the beam breadth which is 200mm. The column shape is square thus the size of the column is 200 mm x 200 mm. For pad footing, the size obtained from the formula equation and the size recorded for this pad footing design is 1500 mm length and the thickness of pad footing is 150 mm. The staircase size is designed based on the provided architectural drawing.